Optimizing learning effectiveness through literacy-oriented teaching materials with quantum teaching in food and nutrition data analysis courses - Haryana, Nila Reswari; Rukmana , Erni; Purba, Edy Marjuang; Fransiari, M.Edwin; Wahyuningrum, Diah Retno (ARKA INSTITUTE, 2025)
This study aimed to optimize learning effectiveness in the Food and Nutrition Data Analysis course through the development of literacy-oriented teaching materials with a Quantum Teaching approach. The research employed a Research and Development (R&D) method using the 4D model: Define, Design, Develop, and Disseminate. The Define stage involved a needs analysis of 60 nutrition students, revealing that 88.5% required interactive teaching materials with step-by-step practical guidance. In the Develop stage, the teaching materials were validated by content and media experts, yielding scores of 91.25% and 89.50%, respectively, which fall into the “very feasible” category. The Disseminate stage involved limited implementation in one class, showing an increase in average student engagement scores from 73.40 to 88.20 and comprehension test scores from 71.85 to 87.45. These findings demonstrate that the developed materials effectively enhance student participation and mastery of data analysis concepts. This innovation addresses the gap in practical-oriented learning resources for nutrition students, aligning with curriculum demands and 21st-century learning skills. The developed materials are expected to improve competence in analyzing food and nutrition data, thereby supporting academic success and professional readiness.